Controlling Unnecessary Laboratory Investigation Requests for Inpatients of General Internal Medicine - Estaitieh , Osama; Uddin, Naveed (Journal of Liaquat University of Medical & Health Sciences, 2025)
Objective: To reduce unnecessary laboratory investigations by more than 15% over three months in the general internal medicine inpatient service at King Fahad Armed Forces Hospital (KFAFH), Jeddah, while maintaining patient safety and improving cost-effectiveness. Methodology: A 12-week prospective interventional study was designed for January-March 2025, at KFAFH, Jeddah, Saudi Arabia. Patients admitted under internal medicine were included, while critically ill, surgical, or non-internal medicine admissions were excluded from analysis. A randomized sample of 200 patients was divided into two groups: 100 in the control group and 100 in the intervention group. For intervention groups, targeted education was provided to residents and registrars, with structured discussions during ward patient visit rounds, and the placement of visual reminders, including posters, banners, and images, in the clinical work area. The frequency of commonly requested laboratory investigations, including complete blood counts (CBCs), serum electrolytes, and liver function tests, was monitored throughout the study. Results: A comparative analysis showed a statistically significant reduction in laboratory investigation requests in the intervention group compared with the control (p<0.0001). This was further observed in the cost-effectiveness, with savings of SAR 86,600 per 100 patients. Interestingly, the reduction in the number of investigations did not affect patient outcomes, indicating that the quality and safety of care were maintained. Conclusion: The study demonstrates that straightforward, multidisciplinary interventions can substantially reduce the overutilization of laboratory tests while providing cost-effective healthcare delivery, aligned with principles of high-value without compromising safety.